2019
DOI: 10.1186/s12935-019-0974-z
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel regulation of RUVBL2 expression predicts poor prognosis in hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) is the second-most lethal cancer worldwide with a complex pathogenesis. RuvB-like 2 (RUVBL2) was previously found to contribute to hepatocarcinogenesis. However, its expression, regulation and clinical significance have not been systematically evaluated in a large number of clinical samples. Methods Here, we performed a comprehensive analysis of RUVBL2 based on multiple datasets from 371 live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In healthy cells, these ATPases are located strictly in the nucleus, but in tumor cells, they are also present in the cytoplasm. This dual localization seems to be necessary for tumor cell survival and tumorigenicity [ 77 ], which leads to shorter survival of patients with HCC [ 81 ].…”
Section: Dna Repairing (Moc-4)mentioning
confidence: 99%
“…In healthy cells, these ATPases are located strictly in the nucleus, but in tumor cells, they are also present in the cytoplasm. This dual localization seems to be necessary for tumor cell survival and tumorigenicity [ 77 ], which leads to shorter survival of patients with HCC [ 81 ].…”
Section: Dna Repairing (Moc-4)mentioning
confidence: 99%
“…Reptin was overexpressed in gastric tissue ( Li et al, 2010 ), and its high expression was related to advanced nodal disease in colon cancer patients ( Flavin et al, 2011 ). For hepatocellular liver carcinoma, overexpressed Reptin is necessary for hepatocyte proliferation ( Javary et al, 2021 ), and it could be used to predict poor prognosis ( Yan et al, 2019 ). Within the excretory system, a previous study showed that overexpressed Reptin is related to the poor differentiation of RCC cells and portends poor outcomes for patients ( Ren et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…RUVBL2 represents RuvB-like 2 protein, deregulation of which in hepatocellular carcinoma is in uenced at the genomic, epigenetic and transcriptional levels. It has been suggested as a promising prognostic marker as well as a therapeutic target for hepatocellular carcinoma [33] . Beside these, the connection between the other genes and laryngeal cancer are not clear yet.…”
Section: Discussionmentioning
confidence: 99%